Penerapan Kursus Berbasis Rapid Rural Appraisal Sebagai Upaya Internasionalisasi Konten Media Pembelajaran Augmented Reality - Abdul Rahman Prasetyo; Fikri Aulia; Fuad Indra Kusuma; Mohamad Firzon Ainur Roziqin; Nila Rahmawati; Eka Putri Surya; Alby Aruna; Adinda Marcelliantika (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to develop and implement a Rapid Rural Appraisal (RRA) based course to internationalize augmented reality (AR) based learning media content. The RRA method is used to identify international needs and preferences for AR learning content. The results of RRA become the basis for developing strategies that include content development, platforms, marketing and promotions. Implementation involves developer training, international collaboration, and regular evaluation and monitoring to ensure successful internationalization. The findings suggest that the integration of local cultural and linguistic elements in AR content as well as the use of platforms that support multilingualism can increase user engagement in international markets. Evaluations also show increased understanding and appreciation of AR learning materials in various countries.